GLASS CLEANING WORK PRODUCTIVITY ANALYSISBUILDING USING ROPE ACCESS METHOD (CASE STUDY GLASS CLEANING OF SEMARANG STATE UNIVERSITY HOUSE OF SCIENCE BUILDING) - Suwandi, Putri Anggi Permata; Syakur, Asy (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Abstract.The need for buildings for various activities is increasing from time to time, the rapid construction of new buildings is generally not accompanied by an increase in maintenance and maintenance activities. Therefore, building maintenance is very important after the building is completed. To clean buildings, many methods are used to clean one of them is the rope access method, therefore in this analysis the researcher will look for the productivity of building cleaning using the rope access method, besides that researchers also have to observe how the procedures for installing safety equipment are used by workers. in the rope access method. To determine work productivity, researchers use the time study method to determine the time needed by workers to complete a job, then researchers will compare the value of worker productivity with the scaffolding method. After the researcher conducted the research, the researcher had data in the form of time which was then converted into m2/person/day. After that, researchers will find out how much the productivity ratio of each of these methods is. After recording the time value and converting it to m2/person/day, the result was found to be more productive using the rope access method because judging from the results of the researcher, it was found that the scaffolding work took longer because the higher the building, the longer the process of work and scaffolding installation. therefore,Keywords: Productivity of Building Glass Cleaning Jobs Using the Rope Access Method.